-6 + 6 = 0
0 + -2x = 12 + 6 -2x = 12 + 64x+2(x-3)=8x+12 is our main problem right? so...
4x + (-3 * 2 + x * 2) = 8x + 12
4x + (-6 + 2x) = 8x + 12
So next we do:
-6 + 4x + 2x = 8x + 12
Reorder the terms :) -6 + 6x = 12 + 8x
Now were going to solve for x
-6 + -2x = 12 + 8x + -8x
8x + -8x = 0
-6 + -2x = 12 + 0
-6 + -2x = 12
-6 + 6 = 0
0 + -2x = 12 + 6
-2x = 12 + 6=
-2x = 18
so now were just going to divide each side by -2
and so thats going to be like this
-2x = 18
/ -2 /-2
0 -9
so whats left over is x = -9
So your answer is A.